Spanish history and female characters. Representations of women in Spanish historical fiction - Chicharro-Merayo, Mar (Convergencia Revista de Ciencias Sociales, 2018)
This article provides some thoughts on how serialized fiction may be utilized to reconstruct history. More specifically, it considers how some television series have helped to make a re-reading of past Spanish society by focusing on female characters. Three pieces of historical fiction were thoroughly analyzed from a semantic perspective. These series reconstructed different periods in Spanish history ( Amar en tiempos revueltos [ Loving in Troubled Times ], La Señora [ The Lady ] and 14 de abril. La República [ April 14, the Republic ]. This article holds that these stories articulate an interconnected representation of social change in Spain, with a leading role being allocated to female figures. They depict increasingly empowered women characters who had an increasing presence in the public and, particularly, in the political sphere. Qualitative content analysis was used to unravel the narrative and semantics of these audio-visual texts.